Brachistochrone Bowl‐Inspired Hybrid Nanogenerator Integrated with Physio‐Electrochemical Multisensors for Self‐Sustainable Smart Pool Monitoring Systems (Adv. Energy Mater. 14/2023). Issue 14 (13th April 2023) - Maharjan, Pukar; Bhatta, Trilochan; Hui, Xue; Pradhan, Gagan Bahadur; Song, Hyesu; Shrestha, Kumar; Park, Jae Yeong
Abstract : Smart Pool Monitoring Systems In article number 2203849, Jae Yeong Park and co‐workers develop a brachistochrone bowl‐inspired self‐powered autonomous smart pool monitoring system (SPMS) for real‐time monitoring of the various physico‐electrochemical properties of pool water. The combined effort of the wave energy harvester and water quality sensors in the SPMS aids in maintaining a hygienic and safe swimming environment for both indoor and outdoor platforms.